Overview on biotherapeutic proteins: impact on bioanalysis. (January 2016) - Zhang, Yan J; Luo, Linlin; Desai, Dharmesh D
This article provides an overview of the information and factors relevant to designing bioanalytical strategies in support of in vivo nonclinical and clinical studies of protein therapeutics. The summarized information includes representative types of the therapeutic proteins, their key structural characteristics, the relationship between post-translational modifications and function, issues during purification and formulation, PK of therapeutic proteins and immunogenicity. The effect of each of those on bioanalysis strategy has been pointed out. The impacts of structural variant and 'free'/'bound' forms on PK assessment have been discussed.